Pemanfaatan Keijibutsu sebagai Media Edukasi Karakter pada Siswa SD Maarif NU Mendiro Ungaran - Ai Sumirah Setiawati; Danny Buyung Yudha Prasetya; Budi Setiarjo (IKIP PGRI Bojonegoro, 2022)
ABSTRACTCharacter education is a hotly discussed issue among educators and the public. According to the observations by conducting visits and observations to schools in Japan, there is one concrete, simple, cheap and easy-to- find media in teaching students in schools to have good character. The media is keijibutsu, namely works in the form of pictures or writings that are affixed to the classroom walls. One form of keijibutsu applied at SD Maarif NU Mendiro Ungaran is “thank you” and “my target” written on